1999
DOI: 10.1091/mbc.10.5.1463
|View full text |Cite
|
Sign up to set email alerts
|

The Secretory Route of the Leaderless Protein Interleukin 1β Involves Exocytosis of Endolysosome-related Vesicles

Abstract: Interleukin 1␤ (IL-1␤), a secretory protein lacking a signal peptide, does not follow the classical endoplasmic reticulum-to-Golgi pathway of secretion. Here we provide the evidence for a "leaderless" secretory route that uses regulated exocytosis of preterminal endocytic vesicles to transport cytosolic IL-1␤ out of the cell. Indeed, although most of the IL-1␤ precursor (proIL-1␤) localizes in the cytosol of activated human monocytes, a fraction is contained within vesicles that cofractionate with late endosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
461
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 430 publications
(484 citation statements)
references
References 55 publications
16
461
1
3
Order By: Relevance
“…Overlap between the P2X7R-triggered signaling pathways that regulate lysosome exocytosis and those required for IL-1β secretion has suggested that these lysosomes may comprise a mechanism for non-classical IL-1β secretion [107]. In human monocytes, both events can be blocked by inhibitors that target Ca 2+ -dependent and Ca 2+ -independent phospholipase A 2 and phosphatidylcholine-specific phospholipase C [37].…”
Section: P2x7r-induced Exocytosis Of Secretory Lysosomesmentioning
confidence: 99%
“…Overlap between the P2X7R-triggered signaling pathways that regulate lysosome exocytosis and those required for IL-1β secretion has suggested that these lysosomes may comprise a mechanism for non-classical IL-1β secretion [107]. In human monocytes, both events can be blocked by inhibitors that target Ca 2+ -dependent and Ca 2+ -independent phospholipase A 2 and phosphatidylcholine-specific phospholipase C [37].…”
Section: P2x7r-induced Exocytosis Of Secretory Lysosomesmentioning
confidence: 99%
“…Recent intriguing evidence implicates endolysosomal vesicles in the non-classical exocytosis of a "signal peptide-less" protein from mammalian cells (Andrei et al 1999). Interleukin 1b is translocated from the cytosol into these vesicles and later secreted in response to extracellular ATP and osmotic conditions.…”
Section: Is There Early Recycling In Dictyostelium Discoideum?mentioning
confidence: 99%
“…LAMP1 (CD107a), LAMP2 (CD107b), LAMP3 (CD63), and LimpII are prevailing isoforms, also expressed in humans. Although LAMPs are localized preferentially to the cytoplasmic compartment, alternate traffic of LAMP1 to the plasma membrane has been identified during cytokine exocytosis (17). Similarly, plasma membrane targeting has been identified for LAMP2, and both LAMP2 and LAMP1 expressed at the cell surface participate in cell-mediated adhesion to the endothelium (18).…”
Section: Introductionmentioning
confidence: 99%